Dari Konfrontasi ke Rekonsiliasi: Dinamika Hubungan Diplomatik Indonesia-China, 1965-1990 - Arum Nur Khasanah (PT Inovasi Penelitian Terpadu, 2025)
This paper aims to examine the dynamics of diplomatic relations between Indonesia and China from the post-1965 confrontation period to the reconciliation process in 1990. Initially, relations between the two countries deteriorated after the G30S/PKI incident, in which Indonesia accused China of being involved in a coup attempt. As a result, in 1967, Indonesia froze diplomatic relations with China. During the New Order era, relations between the two countries remained frozen, marked by suspicion of the spread of communism. However, political and economic changes in both countries encouraged efforts to restore relations. In the late 1980s, with a bilateral diplomatic approach and encouragement of economic cooperation, Indonesia and China began to reopen communication channels, culminating in the normalization of relations in 1990. This process was continued with the strengthening of strategic partnerships, especially in the fields of trade and economy. In conclusion, the Indonesia-China relationship shows that the dynamics of international politics are greatly influenced by domestic and global factors, and bilateral diplomacy can be an important tool to end tensions and build mutually beneficial cooperation.